Produção de biogás a partir da codigestão da cama de frango e água residuária de abatedouro de suínos - Venzon, Simoni Spohr (2017)
Along with the expansion of poultry activity, expressive amounts of poultry litter are generated every year, reaching 100 million tons. An alternative for the disposal of this residue is its use as a substrate for anaerobic biodigestion, which converts organic matter into biogas and digestate, with high nutritive value that can be used as biofertilizer. Because it is a solid residue with low humidity, to facilitate digestion, currently, large amounts of potable water are used. In this study, potable water was replaced by another liquid residue, swine wastewater, highlighting a co-digestion. Co-digestion of the poultry litter with the swine effluent was performed in a horizontal tubular anaerobic reactor with semi-continuous feed, operated at room temperature. By means of the application of a central rotational compound design, the biogas production was studied according to the operational parameters: volatile solids fed, in concentrations ranging from 2 to 8%, and hydraulic retention time, in intervals of 2.95 to 17.05 days. The effluent with low concentrations of nitrogen, total solids and alkalinity together with the reduced concentrations of Ca, K, Zn and absence of Cu can be used in co-digestion with the chicken litter, imparting humidity and neutralizing the toxicity of inhibitory compounds. Biogas production in all biodigesters started on the first day of operation and stabilized soon after the adaptation period (100 h), due to the good quality of the inoculum that had previously been acclimatized. The biogas production rate ranged from 73.69 to 295.26 dm3.kgSVal-1. An increase in biogas production rate can be achieved with high periods of hydraulic retention and with a lower concentration of volatile solids fed to the digester. The highest biogas production rate, with 48% methane, was obtained in a reactor fed with 2.87% volatile solids and hydraulic retention time of 15 days, yielding an energy potential of 0.034 MJ.day-1. The obtained statistical model was able to explain in 90% the experimental data and can be used in the prediction of the biogas production from co-digestion with poultry litter and swine wastewater. Even with the high alkalinity from the poultry litter, it was not enough to buffer the accumulation of volatile acids, occurring decrease in pH. In all reactors the carbon: nitrogen ratio in the substrates remained around 32.04±0.01 and there was no increase in pH, indicating no inhibition by ammonia. In all the reactors there was reduction of organic and nitrogen loads. Even with high organic load and in the presence of plant and soil nutrients, the digestates can be used as fertilizer with economic and ecological benefits.